A Genetic Linkage Map of the Apicomplexan Protozoan Parasite Eimeria tenella - Shirley, Martin W.; Harvey, Dora A. (Genome Research, 2000)
Apicomplexan protozoan parasites have complex life cycles that involve phases of asexual and sexual reproduction. Some genera have intermediate insect hosts, for example, Plasmodium spp. (the cause of malaria), but related genera such as Eimeria spp. (causative agents of coccidiosis in poultry) have a direct life cycle occurring in only a single host. Mechanisms that regulate the life cycles of apicomplexan parasites are unknown, but the intracellular growth of avian Eimeria spp. is easily shortened by serial selection for the first parasites to complete the transition from asexual to sexual reproduction (to yield so-called precocious lines). To investigate the genetic basis of such an abbreviated life cycle, we have used the species E. tenella and analyzed the inheritance of 443 polymorphic DNA markers in 22 recombinant cloned progeny derived from a cross between parents that had selectable phenotypes of precocious development or resistance to an anticoccidial drug. The markers were placed in 16 linkage groups (which defined 12 chromosomes) and a further 57 unlinked groups. Two linkage groups showed an association (P = .0105) with the traits of precocious development or drug-resistance and were mapped to chromosome 2 (ca 1.2 Mbp) and chromosome 1 (ca 1.0 Mbp), respectively. The map provides a framework for further studies on the identification of genetic loci implicated in the regulation of the life cycle of an important protozoan parasite and a representative of a major taxonomic group.[A table with the segregation data is available as an online supplement at http://www.genome.org.]
10.1101/gr.149200